Static and dynamic evaluation of elastic properties of Sofia sand and Toyoura sand by sophisticated triaxial tests - Milev Nikolay; Koseki Junichi (Građevinski Materijali i Konstrukcije, 2018)
The main purpose of the presented paper is to show the advantages and disadvantages of evaluating the small strain stiffness of cohesionless soils by means of different types of laboratory equipment. A series of consolidated undrained cyclic triaxial testes have been performed on saturated specimens made of Toyoura sand and Sofia sand having various dry densities. Relatively small unloading-reloading cycles have been applied on the specimens in order to obtain the 'static' Young's modulus. Furthermore two types of wave propagation techniques have been adopted for the sake of a 'dynamic' Young's modulus determination: one is using bender elements in the cross section of the specimen and the other is using trigger elements in the longitudinal section of the specimen to excite shear waves and two accelerometers which capture the waves' arrival in two points. On one hand the difference between the two types of dynamic measurements and static measurements is discussed and on the other hand some relationships between the abovementioned approaches are given.